Association Between Quality of Prenatal Care and Patient Satisfaction Among Pregnant Women at Kenali Besar Primary Health Center - Carolina Pinem, Jessy Putri; Mawarti, Indah; Sari, Putri Irwanti; Yusnilawati; Mutmainnah, Muthia (Program Studi Keperawatan Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2026)
Introduction: Healthcare service quality is an important indicator in assessing the quality of primary care facilities such as public health centers. The Antenatal Care (ANC) program is a crucial strategy in reducing the Maternal Mortality Rate (MMR), where the satisfaction of pregnant women reflects the fulfillment of patients' clinical and psychological expectations. This study aims to determine the relationship between the quality of ANC health services and the satisfaction level of pregnant women at the Kenali Besar Public Health Center, Jambi City, in 2026. Methods: This type of research is quantitative with a cross-sectional design, using a purposive sampling technique to obtain a sample of 59 respondents. Results: The univariate research results showed that the majority of respondents rated the quality of ANC services in the good category (57,6%) and felt satisfied with the services received (88.1%). The results of the bivariate test using Chi-Square obtained a p-value of 0.035 (<0.05) with an Odds Ratio (OR) of 10.421. This indicates a significant difference in perception, where pregnant women who receive poor service are 4.4 times more likely to feel less satisfied. Conclusion: It can be concluded that there is a significant relationship between the quality of health services and the satisfaction level of pregnant women at the Kenali Besar Public Health Center, Jambi City.